Using sensor orientation information for computational head stabilisation in 3D Electromagnetic Articulography (EMA) - Kroos, Christian (ISCA, 2009)
We propose a new simple algorithm to make use of the sensor orientation information in 3D Electromagnetic Articulography (EMA) for computational head stabilisation. The algorithm also provides a well-defined procedure in the case where only two sensors are available for head motion tracking and allows for the combining of position coordinates and orientation angles for head stabilisation with an equal weighting of each kind of information. An evaluation showed that the method using the orientation angles produced the most reliable results.